Two new oak gall wasp species (Hymenoptera: Cynipidae, Cynipini) from Quercus pontica (Fagaceae) in Turkey - Azmaz, Musa; Katilmiş, Yusuf (Zootaxa, 2021)
Two new species of oak gall wasp, Andricus mammadovi Azmaz & Katılmış sp. n. sexual generation and Cynips fatihi Azmaz & Katılmış sp. n. asexual generation (Cynipidae: Cynipini) are described from the eastern Black Sea region in Turkey. These species induce galls on Quercus pontica K.Koch representing the first record of cynipids associated with the natural Q. pontica population in Turkey. SEM images, photos of the host galls, and data on the diagnosis, distribution, and biology of both new species are provided.